2009
DOI: 10.2202/1935-1682.2134
|View full text |Cite
|
Sign up to set email alerts
|

American Idol: Evidence on Same-Race Preferences

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…He found that the racial composition of the contestants affects the viewing of black and non-black households, such that as the share of black contestants increases, the black households' rating increases, whereas the non-black households' rating decreases. Lee (2006) also found strong evidence for same-race preferences in the 1 Source: Wikipedia (http://en.wikipedia.org/wiki/American_Idol).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…He found that the racial composition of the contestants affects the viewing of black and non-black households, such that as the share of black contestants increases, the black households' rating increases, whereas the non-black households' rating decreases. Lee (2006) also found strong evidence for same-race preferences in the 1 Source: Wikipedia (http://en.wikipedia.org/wiki/American_Idol).…”
Section: Introductionmentioning
confidence: 92%
“…to the best of our knowledge, there have not been any economics studies examining the relationship between social networks and viewers' behavior in reality TV shows, except for the aforementioned study by Lee (2006) on same-race preferences. The economics studies that do exist on reality shows investigate the structure and rules of the contest.…”
Section: Introductionmentioning
confidence: 99%
“…Television game shows are a typical example, where discriminatory choices of participants can be studied in a controlled environment. Discrimination analysis has been reported in (Antonovics et al, 2005Bagues & Villadoniga, 2008;Levitt, 2004), with data gathered from the Weakest Link game show, in (Lee, 2009) with data from American Idol TV contest show, and in (J. A.…”
Section: Controlled Experimentsmentioning
confidence: 99%
“…the "mating taboo" in Wong, 2003 or the speed dating preferences in Fishman et al, 2006), among very young kids (e.g. Hraba and Grant, 1970) or among audiences of television shows (Dates, 1980, Lee, 2006). 7 The difference in the use of informal job networks among professions is also documented.…”
Section: Intra-group Homophilymentioning
confidence: 99%
“…it actually solves the maximization problem (38). Define the feasible set C = {μ R ∈ [0, 1], μ G ∈ [0, 1]|g(μ R , μ G ) = 0}.…”
Section: A Proofsmentioning
confidence: 99%